2019
DOI: 10.3390/genes10120993
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Genes Involved in Embryo Development and Differential Oil Accumulation in Two Contrasting Maize Genotypes

Abstract: Maize is an important oil seed crop and a major food crop in different parts of the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…During the filling stage, sucrose and amino acids are converted to starch and storage proteins. The genes related to amino acid biosynthesis accumulate to their optimal level from DAP 10 [34], starch accumulation peaks at DAP 15 and then remains steady [35,36], and oil concentration reaches its peak level on DAP 30 [37]. At the end of seed filling, seed maturation starts with the progressive loss of water [38].…”
Section: Discussionmentioning
confidence: 99%
“…During the filling stage, sucrose and amino acids are converted to starch and storage proteins. The genes related to amino acid biosynthesis accumulate to their optimal level from DAP 10 [34], starch accumulation peaks at DAP 15 and then remains steady [35,36], and oil concentration reaches its peak level on DAP 30 [37]. At the end of seed filling, seed maturation starts with the progressive loss of water [38].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the comparison between two contrasting maize genotypes revealed that many vital TAG biosynthetic genes showed differential expression between high oil content (HOC) and low oil content (LOC) maize. GPAT , DGAT , and PDAT genes were up-regulated, but GPDH was down-regulated in HOC [ 54 ]. These findings were consistent with our conclusion from comparisons across multiple species, which implied that GPAT , DGAT , GPDH , PDAT , and WRI1 genes played vital roles in seed oil biosynthesis in maize kernels.…”
Section: Discussionmentioning
confidence: 99%
“…Maize kernel consists of developed embryo and endosperm, and the oil mainly stored in embryo. Maize has relatively large seeds but unfortunately the oil content of maize kernels is extremely low, which is approximately 4%–5% of the seed dry weight [ 54 ]. Nevertheless, castor bean, which had developed embryo and endosperm as well, had high oil content and accumulated plenty of oil in the endosperm.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the relatively low cost of Illumina sequencing has made it easier to perform global transcriptome profiling in any plant species. This helps us to understand the molecular mechanisms and key genes involved in defining key agronomic and quality traits [5,[21][22][23]. For example, tyrosine hydroxylase CYP76AD1 and 4,5-DOPA dioxygenase DODA, related to betalain biosynthesis, were identified as the key genes controlling the red pulp color of pitaya using the transcriptome approach [5].…”
Section: Introductionmentioning
confidence: 99%